2021
DOI: 10.1016/j.jpsychires.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotion regulation and mental health difficulties on health behaviours during COVID19

Abstract: The COVID-19 outbreak is having a profound impact on individuals' psychological and physical wellbeing. The aim of this study was to assess the extent of this impact and its mechanisms on a sample of adults living in Italy during the first lockdown (April–May 2020). Two hundred ninety-two individuals (67.1% females) were recruited from the community through social media. They completed baseline online questionnaires to collect demographic information, data on past and present general health and health behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…However, home-based physical activity should be strongly encouraged, as it is a viable and important proposal for providing immediate and long-term health benefits, especially for vulnerable groups and/or during emergency periods of restricted social contact, as experienced during the COVID-19 pandemic [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, home-based physical activity should be strongly encouraged, as it is a viable and important proposal for providing immediate and long-term health benefits, especially for vulnerable groups and/or during emergency periods of restricted social contact, as experienced during the COVID-19 pandemic [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human beings are said to be fragile psychologically. Fluctuations of emotions [22] are often closely intertwined with mental issues. When physical surroundings around individuals differ, it also impacts their minds [23].…”
Section: Psychologicalmentioning
confidence: 99%
“…with greater resilience (i.e., the ability to seek enjoyable activities and social support and feelings of hope and resourcefulness). 24 Cognitive reappraisal is a technique that may be learned and utilized to mitigate the impact of stress on an individual's well-being, including stress induced by a pandemic. The current study revealed that patients with psychological problems are especially susceptible and in need of care, particularly during the current COVID-19 pandemic.…”
Section: Original Article Smjmentioning
confidence: 99%